2003
DOI: 10.1128/jb.185.7.2259-2266.2003
|View full text |Cite
|
Sign up to set email alerts
|

YscP and YscU Regulate Substrate Specificity of theYersiniaType III Secretion System

Abstract: Pathogenic Yersinia species use a type III secretion system to inhibit phagocytosis by eukaryotic cells. At 37°C, the secretion system is assembled, forming a needle-like structure on the bacterial cell surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
138
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(152 citation statements)
references
References 51 publications
12
138
0
Order By: Relevance
“…Type III virulence homologues of flhB apparently play a similar role in switching export specificity from needle-type substrates to later substrates. In Yersinia pseudotuberculosis, mutations in the cytoplasmic domain of the inner membrane protein YscU (FlhB homologue) suppress the yscP (fliK homologue) polyneedle phenotype (39). In addition, it has been shown that specific cleavage occurs at the equivalent site (Asn-263/Pro-264) of YscU, and mutations at this site have complex effects on late substrate secretion and growth (40).…”
Section: Discussionmentioning
confidence: 99%
“…Type III virulence homologues of flhB apparently play a similar role in switching export specificity from needle-type substrates to later substrates. In Yersinia pseudotuberculosis, mutations in the cytoplasmic domain of the inner membrane protein YscU (FlhB homologue) suppress the yscP (fliK homologue) polyneedle phenotype (39). In addition, it has been shown that specific cleavage occurs at the equivalent site (Asn-263/Pro-264) of YscU, and mutations at this site have complex effects on late substrate secretion and growth (40).…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Therefore, it has been proposed that autocleavage of the YscU cytoplasmic domain results in a conformational change that triggers the recognition and export of translocators at the proper time during the assembly of the type III secretion apparatus. 9,[11][12][13] We report here the crystal structures of two noncleaved forms of YscU, YscU N263A and YscU N263A/ P264A , and an atomic resolution structure of the wildtype cleaved form, YscU cleaved , to elucidate structural changes that occur upon cleavage. These crystallographic studies reveal the conformational changes induced upon auto-cleavage of YscU and provide structural insights into the cleavage mechanism, at very high resolution, that confirm and extend the information gleaned from structures of YscU homologs from Shigella flexneri (Spa40), enteropathogenic Escherichia coli (EscU) and Salmonella typhimurium (SpaS).…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is corroborated by the finding that single point mutations in the C-terminal regions of FlhB, YscU, and homologs can restore the wild-type phenotype in T3S4 mutants of S. Typhimurium, Y. pseudotuberculosis, EPEC, and X. campestris pv. vesicatoria (148,298,330,602,626) (Table 7). It is assumed that the introduction of point mutations into the C-terminal domains of YscU/FlhB family members leads to a conformational change that is permissive for the substrate specificity switch.…”
Section: T3s4 Proteins and Their Interplay With Yscu/flhb Family Membersmentioning
confidence: 99%